Measuring changes in Mozambique’s agri-food system - International Food Policy Research Institute; Xinshen Diao; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James (International Food Policy Research Institute, 2023)
Transformation of the agri-food system (AFS) is a leading pathway to achieve the USG Global Food Security Strategy Objective 1 of “Inclusive agriculture-led growth”. The AFS encompasses the primary agricultural sector, as well as all upstream and downstream agriculture-related activities. An expansion of the AFS’s off-farm components is central to the process of agricultural transformation and is strongly associated with economic development. The Percent change in value-added in the agri-food system (AgGDP+) and Employment in the agri-food system (AgEMP+) indicators are useful to track this process.